In-situ observations of wave- and current-supported fluid mud dynamics on a hyperturbid macrotidal mudflat - Li, Mingliang; Chen, Dezhi; Wu, Hao; Tang, Jieping; Zhang, Yiyi; Luo, Feng; Gou, Fugang; Gong, Xulong; Wang, Ya Ping (Frontiers in Marine Science, 2024)
Wave- and current-supported fluid mud on gently sloped continental shelves represents a type of sediment gravity flow capable of rapidly transporting substantial sediment over short periods, significantly contributing to coastal geomorphic evolution. To investigate the dynamics of intertidal fluid mud events, in-situ observations were conducted from May 9 to May 18, 2017, using a seabed tripod system at the lower intertidal flat of the central Jiangsu coast, China. Fluid mud was observed following a medium wind-wave event, with a maximum significant wave height of 0.42 m. The liquefied seabed, loosened by liquefaction, facilitated bed erosion and sediment resuspension. Fluid mud layers, with mean suspended sediment concentrations (SSCs) exceeding 10 g/L, periodically formed during high slack tide, early flood, and late ebb phases. These layers varied in thickness from 4 cm to 20 cm and exhibited strong stratification caused by suspended sediment. Fluid mud disappeared when the bottom turbulence kinetic energy exceeded a threshold of 0.00045 m²/s² due to an increase in current velocity. The downslope movement of intertidal fluid mud was estimated using a theoretical buoyancy-friction model and validated by observed offshore-directed velocity jets at 0.1 m above the seabed during high slack tide phases. Additionally, onshore winds favored fluid mud formation during early flood phases, while offshore winds favored it during late ebb phases. These observations suggest that fluid mud can form on intertidal flats under conditions where tidal flows and winds align, contributing to a deeper understanding of the formation mechanisms of shallow gravity flows and the improvement of sediment transport models.